CCNA Exam. - McDowell, Jeremy (Manning Publications, 2023)
The Cisco Certified Network Associate or CCNA exam validates your knowledge of fundamental networking concepts, and can help build your IT resume. Part 8: Wireless LANs and Network Automation is the eighth and final part of the eight-part CCNA course. The course starts with the basics and guides you through the six domains of the CCNA exam: Network Fundamentals Network Access IP Connectivity IP Services Security Fundamentals Automation and Programmability Each lesson builds on the previous parts, guiding you seamlessly through all the topics you need to know to pass the CCNA exam. You'll also get these additional resources to ensure your success: Flashcard decks to help you remember what you have studied in each video Lesson slides in .PDF format to review after watching each video lesson Practical network simulation exercises using Cisco Packet Tracer to give you hands-on practice to develop your networking skills This course has already helped many students all over the world to pass the CCNA exam, and you can be the next one. The course teaches you not only what you need to know to pass the exam, but also fundamental networking knowledge that applies to all areas of IT.